Digital Branding Strategies of Islamic Boarding Schools: A Social Media Marketing Content Analysis - Unzilah Khumairotusshiyamah; Muhammad Kholilurrohman; Muhammad Thoiful Abrar; Zackyl Musthofa; Siti Khofsah; Ida Kusumawati; Akmal Mundiri; Ola Fedda Mona Denona (Journal of Educational Management Research, 2026)
This study aims to analyze the digital branding strategy of Islamic boarding schools through marketing content on Instagram, specifically in building the institution's image and attracting public interest. The research method used is a qualitative approach with content analysis of posts on the Islamic boarding school's Instagram account, supported by interviews and observations to deepen the data. The results show that the Islamic boarding school's digital branding strategy is carried out through three main patterns: highlighting religious and educational values, using attractive and consistent visuals, and utilizing student testimonials and activities as a form of promotion. Educational and inspirational content has proven more effective in building engagement with the audience. In addition, Instagram plays a significant role as the primary medium in shaping the modern image of Islamic boarding schools without abandoning their traditional values. The implication of this study is the importance of professional social media content management so that Islamic boarding schools can compete in the digital era, while strengthening institutional identity in an increasingly digital-savvy society.